2004
DOI: 10.1897/03-393
|View full text |Cite
|
Sign up to set email alerts
|

Water‐extractability, free ion activity, and pH explain cadmium sorption and toxicity to Folsomia candida (Collembola) in seven soil‐pH combinations

Abstract: Toxicity of cadmium to Folsomia candida was determined in soils at different pHs (3.5, 5.0, and 6.5). The Langmuir sorption constant (K(L)), based on pore-water or water-extractable concentrations, showed a pH-related increase of cadmium sorption that was most pronounced when using free Cd2+ ion activities ([Cd2+]s). Two-species Langmuir isotherms that used total cadmium concentration ([Cd]) or [Cd2+] and pH in the water-extractable fractions gave the best description of cadmium sorption on all soils together.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
58
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 43 publications
9
58
0
Order By: Relevance
“…The evidence that soil properties such as soil organic matter content, clay content and specifically pH do affect the bioavailability and toxicity of metals in biota (e.g. Spurgeon and Hopkin 1996;Van Gestel and Koolhaas 2004), is hardly accounted for in the critical limits assessment.…”
Section: Need Of Critical Limits For Metals In Soil and Soil Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence that soil properties such as soil organic matter content, clay content and specifically pH do affect the bioavailability and toxicity of metals in biota (e.g. Spurgeon and Hopkin 1996;Van Gestel and Koolhaas 2004), is hardly accounted for in the critical limits assessment.…”
Section: Need Of Critical Limits For Metals In Soil and Soil Solutionmentioning
confidence: 99%
“…The evidence that soil properties such as soil organic matter content, clay content and specifically pH do affect the bioavailability and toxicity of metals in biota (e.g. Spurgeon and Hopkin 1996;Van Gestel and Koolhaas 2004), is hardly accounted for in the critical limits assessment.Since effects on micro organisms, plants and, to a large extent, also to invertebrates occur through the soil solution, in particular by the free metal ions, an approach to set critical limits for FMI is in particularly appropriate to evaluate the risks of effects. …”
mentioning
confidence: 99%
“…According to Van Gestel and Koolhaas (2004), the main route for metal(loid) uptake by microarthropods is the soil solution, which contains fungi and which is in contact with the soil organic matter. Soil solution is actually considered as a major exposure pathway for the majority of pedofauna.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only 1 study has investigated the applicability of BLMs for the springtail F. candida [17]. The authors showed that the free Cd ion is the most important Cd species for predicting uptake and toxicity in this organism and showed that Cd toxicity may be affected by pH and Ca content.…”
Section: Introductionmentioning
confidence: 99%